Design of a new somatosensory stimulus delivery system to assess hand functions - Tan, Cher Yang (Nanyang Technological University, 2022)
Neurological injury such as stroke typically results in impaired motion and sensation in upper limbs. However, sensory rehabilitation for the hand is often neglected. Main causes cited are lack of time and lack of resources to appropriate quantified assessments. In this project, a prototype was designed to provide two different kinds of stimuli to the thumb, index and middle finger of the right hand. These stimuli were rotation about the metacarpal joint, and thermotactile stimulus at the distal phalanx of the fingers. These stimuli were provided using a remote centre of motion mechanism and Peltier modules. The accuracy of the prototype in rotating the fingers about the metacarpal joint was assessed using a potentiometer jig for the thumb and an accelerometer for the index and middle finger. The accuracy of the prototype in providing thermotactile stimuli was verified using a precise infrared thermometer. When referenced against these external measuring devices, the level of stimuli reported by the prototype against the measurement of these external devices were consistent with one another, showcasing the accuracy of the prototype in providing accurate levels of stimuli. Preparation time was tested with a group of healthy adults and proven to be short with an average time of 2 minutes . In conclusion, the prototype was evaluated to be able to provide accurate level of stimuli for two of the three stimuli that was to be provided. Several limitations were identified. Firstly, materials used for the construction of the prototype were not strong and thus the prototype could bend and flex. Next, large amounts of electronics not connected using a printed circuit board caused the prototype to be bulky. The temperature range of the thermo tactile stimuli and the speed at which it reached its setpoint could be increased.